REKONSTRUKSI KONSEP ECONOMIC VALUE OF TIME SEBAGAI ALTERNATIF TIME VALUE OF MONEY DALAM PEMBIAYAAN MURABAHAH - Imelda Aisyah; Laily Hidayati Rosyidi (Jurnal Ekonomi Syariah Darussalam, 2025)
The application of the Time Value of Money (TVM) concept in Murabahah financing within Islamic banking is often considered contradictory to Sharia principles due to the potential for usury (riba). This research aims to reconstruct the Economic Value of Time (EVT) concept as a paradigmatic alternative to TVM for determining Murabahah financing margins in Islamic banking. This study employs a systematic literature review with a descriptive qualitative approach, synthesizing literature that compares TVM and EVT within the context of contemporary fiqh muamalah (2021–2026). The literature review indicates that EVT shifts the basis of margin determination from time-based pricing to productivity-based pricing. The synthesis results demonstrate that the Murabahah margin should be calculated based on economic value-added and the projected velocity of money from the financed real sector, rather than based on time annuities as practiced in conventional credit. This is consistent with the DSN-MUI Fatwa No. 153/2022, which recognizes the "price of time" (hisshotan min al-tsaman) only within the framework of actual effort and real business risk, not merely the passage of time. The reconstruction of EVT encourages Islamic banks to transition from fixed return abstraction toward functional intermediation that actively monitors the performance of the customer's business. This not only strengthens Sharia compliance but also enhances the stability of the real financial sector.